PERAN KEPALA SEKOLAH DALAM MENINGKATKAN MUTU PENDIDIKAN DI SMP NEGERI 23 MEDAN - Inka Paramitha (Universitas Islam Negeri Sumatera Utara Medan, 2018)
AbstrakThis research was conducted to describe the role of the principal in improving thequality of education in the country's first secondary school 23. This research was conducted to find out the roles of the principal and the quality of education in teprapkan school principal in improving the quality of education in the country's first secondary school 23. The approach in this research was qualitative in the naturalistic approach to engineering data collection the author uses the dwarf observation, interview and documentation. The data analysis done through the reduction of data, data of the presence, and the withdrawal of the conclusion. While the validity of the guarantor in the author's data use kredebilitas, transferdabilitas, depentabilitas, and konfirmabilitas. Research results: 1. The role of the principal in 23 of the country's first high school Field is a functional teacher who was given the task of leading a school, a place held teaching and learning or the onset of interaction between teachers the member's lessons and students receiving lessons. 2. The principal as an administrator have a relationship very closely with a wide range of administrative management activities. As a leader who claimed to be an administrator of the school principal should have keahliah in the field of administration. 3. Thus the principal managerial performance is the appearance of the work of the principal in the management of the optimization of resources in the school to achieve the goals of the school by implementing the management functions which consists of planning, organizing, implementing and monitoring. For it researchers menyipulkan that the role of the principal in improving the quality of education can be seen from how principal running and requiring teachers in training – training and perform the MGMP. Keywords: The Role Of The Principal, The Quality Of Education